Financial paradigms - Torre, Augusto de la; Ize, Alain (World Bank, Washington, DC, 2012)
What market and regulatory issues led to the subprime crisis? How should prudential regulation be fixed? The answers depend on the interpretative lenses or 'paradigms' through which one sees finance. The agency paradigm, which has dominated recent regulatory policy, seems to be influencing much of the emerging reform agenda. But collective welfare failures particularly externalities and collective cognition failures particularly mood swings were at least as important in driving the crisis. All three paradigms should therefore be integrated into a more balanced policy agenda. But doing so will be difficult because they often have inconsistent policy implications.